2019
DOI: 10.14718/acp.2019.22.2.14
|View full text |Cite
|
Sign up to set email alerts
|

Propiedades psicométricas del Cuestionario de Resiliencia para Niños y Adolescentes en estudiantes mexicanos de bachillerato

Abstract: Se agradece a la Dra. Norma Ivonne González-Arratia López Fuentes, autora del Cuestionario de resiliencia para niños y adolescentes por su generosidad al proporcionar el instrumento para investigación. Al Consejo Nacional de Ciencia y Tecnología de México por la beca de manutención N° 375718 para estudios de doctorado del primer autor, de donde surge el presente estudio. Psychometric properties of the Resilience Questionnaire for children and adolescents in Mexican high school students

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…The scale has five components: self-confidence, equanimity, perseverance, personal satisfaction, and feeling happy alone, the minimum score being twenty-five and the maximum 175 (Wagnild & Young, 1993). In adaptations for adolescent populations, the instrument has shown a reliability level of .90 and adequate levels of adjustment (Bravo-Andrade et al, 2019). In the Colombian university population, the instrument was adapted with a reliability of .846 (Oviedo-Feria, 2017), which was used in the present study because it showed adequate psychometric properties in a population similar to the one studied.…”
Section: Measurements and Proceduresmentioning
confidence: 99%
“…The scale has five components: self-confidence, equanimity, perseverance, personal satisfaction, and feeling happy alone, the minimum score being twenty-five and the maximum 175 (Wagnild & Young, 1993). In adaptations for adolescent populations, the instrument has shown a reliability level of .90 and adequate levels of adjustment (Bravo-Andrade et al, 2019). In the Colombian university population, the instrument was adapted with a reliability of .846 (Oviedo-Feria, 2017), which was used in the present study because it showed adequate psychometric properties in a population similar to the one studied.…”
Section: Measurements and Proceduresmentioning
confidence: 99%
“…Originally, the Resilience Questionnaire was designed to evaluate Mexican children and teenagers [35][36][37][38]; however, because of its relevance in this context, it has been applied to groups of young people [39][40][41] and adults [42][43][44], demonstrating to be a reliable measure of the construct.…”
Section: • Diaphragmatic Breathingmentioning
confidence: 99%
“…Resilience. Resilience was measured through the total score of the Resilience Questionnaire for Children and Adolescents (González-Arratia, 2016) in its revised version for Mexican population (α = .85; Bravo- Andrade et al, 2019). The 18 items were anchored on a Likert scale with five response options ranging from never to always.…”
Section: Instrumentsmentioning
confidence: 99%